2015
DOI: 10.1515/ract-2014-2372
|View full text |Cite
|
Sign up to set email alerts
|

Observations of surface-mediated reduction of Pu(VI) to Pu(IV) on hematite nanoparticles by ATR FT-IR

Abstract: Previous studies have shown that mineral surfaces may facilitate the reduction of plutonium though the mechanisms of the reduction are still unknown. The objective of this study is to use batch sorption and attenuated total reflectance Fourier transform infrared spectroscopy experiments to observe the surface-mediated reduction of plutonium on hematite nanoparticles. These techniques allow for in situ measurement of reduction of plutonium with time and may lead to a better understanding of the mechanisms of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…This is based on previous observations that the solid can be easily removed from solid surfaces with washing. 24 Uranyl stretches were observed also on the both GO electrode surfaces after exposure to CV scanning with the 1mM 238 U electrolyte. In addition to uranyl stretches at 820 cm -1 and 943 cm -1 , strong overlapping peaks were observed on the GO surfaces after CV scanning at 1011 cm -1 and 1092 cm -1 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This is based on previous observations that the solid can be easily removed from solid surfaces with washing. 24 Uranyl stretches were observed also on the both GO electrode surfaces after exposure to CV scanning with the 1mM 238 U electrolyte. In addition to uranyl stretches at 820 cm -1 and 943 cm -1 , strong overlapping peaks were observed on the GO surfaces after CV scanning at 1011 cm -1 and 1092 cm -1 .…”
Section: Resultsmentioning
confidence: 89%
“…which can be ascribed to a hydroxide form of the uranyl, so-called scheopite type structure (UO2)8O2(OH)12•12(H2O)). 24 We hypothesize that the precipitate formed as a result of the presence of aqueous uranyl ions during drying the sample for the ATR-FTIR measuremenst and that the precipitate was not present during the CV scans. This is based on previous observations that the solid can be easily removed from solid surfaces with washing.…”
Section: Resultsmentioning
confidence: 98%
“…The development of Pu IV on a mineral surface in contact with dissolved plutonium, from solutions containing trivalent through pentavalent Pu, has been previously observed. Many of the reported studies have involved iron or manganese bearing surfaces, such that the full redox couple has been assumed to involve the mineral phase itself. , However, similar behavior has also been observed with solutions in contact with redox-inactive mineral surfaces. , Related studies of Pu­(V) to Pu­(IV) reduction on montmorillonite, a redox-inactive mineral surface, show similar characteristics. The reduction was slow, and, on the basis of pH and ionic-strength dependence of the rate, it was hypothesized to involve a proton-mediated surface process .…”
Section: Discussionmentioning
confidence: 85%
“…Because of early suggestions that Pu IV may be the dominant surface species, many of these studies have focused on redox active mineral surfaces, notably those of reducing iron and manganese bearing phases. Assumed to be dependent on relative ion-surface redox couples, both oxidized and reduced , Pu have been identified as surface complexes. Of particular interest are studies involving redox-inactive minerals and related surfaces in which Pu is also found as an oxidized or reduced surface complex relative to its dominant solution speciation, , raising questions about the complementary roles of solution and interfacial chemistry in sorbed Pu speciation.…”
Section: Introductionmentioning
confidence: 99%
“…48 The appearance of shoulders around 1122, 1063 and 1035 cm À1 in the spectrum of PDA-U and 1101 cm À1 in the spectrum of PDA-Pu may indicate the formation of hydroxyl complexes, which exhibit the metal-OH bending mode in the region 1200-700 cm À1 . 39,46,49 In comparison to pristine PDA, PDA-U sample demonstrates a twofold enhancement of the band at 3214 cm À1 and its red shi to 3130 cm À1 . The band at 1588 cm À1 shis to 1610 cm À1 and increases distinctly in the region of C]O stretching vibrations of the carboxylic acid groups and the quinone units.…”
Section: The U(vi) Moieties Uptake From the Gw And Swmentioning
confidence: 99%